Repeat aortic valve surgery: contemporary outcomes and risk stratification. (6th December 2020) - François, Katrien; De Backer, Laurent; Martens, Thomas; Philipsen, Tine; Van Belleghem, Yves; Bové, Thierry
Abstract: OBJECTIVES: Redo aortic valve surgery (rAVS) is performed with increasing frequency, but operative mortality is usually higher compared to that associated with primary aortic valve surgery. We analysed our patients who had rAVS to determine the current outcomes of rAVS as a surgical benchmark in view of the growing interest in transcatheter valve techniques. METHODS: We retrospectively reviewed 148 consecutive patients [median age 67.7 years (interquartile range 54.9–77.6); 68.2% men] who underwent rAVS following aortic valve replacement (81.6%), aortic root replacement (15%) or aortic valve repair (3.4%) between 2000 and 2018. RESULTS: Indications for rAVS were structural valve dysfunction (42.7%), endocarditis (37.8%), non-structural valve dysfunction (17.7%) and aortic aneurysm (2.1%). Valve replacement was performed in 69.7%, and 34 new root procedures were necessary in 23%. Early mortality was 9.5% ( n  = 14). Female gender [odds ratio (OR) 6.16], coronary disease (OR 4.26) and lower creatinine clearance (OR 0.95) were independent predictors of early mortality. Follow-up was 98.6% complete [median 5.9 (interquartile range 1.7–10.9) years]. Survival was 74.1 ± 3.7%, 57.9 ± 5.1% and 43.8 ± 6.1% at 5, 10 and 14 years, respectively. Cox regression analysis revealed female gender [hazard ratio (HR) 1.73], diabetes (HR 1.73), coronary disease (HR 1.62) and peripheral vascular disease (HR 1.98) as independent determinants of late survival. CONCLUSIONS: Despite many urgent situations and advanced New York Heart Association functional class at presentation, rAVS could be performed with acceptable early and late outcomes. Risk factors for survival were female gender, coronary disease and urgency. In this all-comers patient cohort needing rAVS, only a minority would eventually qualify for transcatheter valve-in-valve procedures. Abstract : Increased life expectancy after valve surgery, the ageing population in Western countries and the rising preference for bioprosthetic aortic valves lead to an increasing number of surgical patients presenting for aortic valve reinterventions [1, 2].